2021
DOI: 10.1016/j.nmni.2021.100917
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the COVID-19 pandemic effect on the development of somatic symptoms in patients with mood disorders: a case-control study

Abstract: Somatic symptoms are one of the most common complaints among patients with psychiatric disorders and are considered as one of the most common psychiatric disorders in the new coronavirus pandemic. This study aimed to evaluate the effect of the COVID-19 pandemic on the physical symptoms in patients with mood disorders and compare it with healthy individuals. In this case-control study, 67 patients with mood disorders were referred to the psychiatric clinic of 5 Azar Hospital in Gorgan, who met the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In their study Sanders & Adams, found that notable rate of the caregivers of the Alzheimers disease experienced high levels of grief and depressive symtoms (27,28). However, COVID-19 patients are facing with stitma and discrimination around the globe which can lead to grief process limitations (29).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In their study Sanders & Adams, found that notable rate of the caregivers of the Alzheimers disease experienced high levels of grief and depressive symtoms (27,28). However, COVID-19 patients are facing with stitma and discrimination around the globe which can lead to grief process limitations (29).…”
Section: Discussionmentioning
confidence: 98%
“…Grief reactions may different in different types of death. The studies revealed specific grief charactristics based on the type of death.The results of study conducted by Houck showed the grief reactions among people who mourned from cancer,AIDS related, and suicide were different.However, it was greater in suicide due to its high stigmatization (26) In their study Sanders & Adams, found that notable rate of the caregivers of the Alzheimers disease experienced high levels of grief and depressive symtoms (27,28). However, COVID-19 patients are facing with stitma and discrimination around the globe which can lead to grief process limitations (29).…”
Section: Discussionmentioning
confidence: 99%
“…Second, the findings were obtained in a population sample and cannot be generalized to clinical groups. There is evidence that fear of COVID-19, cyberchondria, and somatization differ between healthy persons and patients with mental and physical diseases ( 64 66 ). The patterns found should be examined in clinical groups including patients with somatoform disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The theory opines that unpleasant objective life conditions such as job loss, health stressors, pandemic lockdown, war, family discord and general stressful life circumstances can negatively affect subjective wellbeing (for example, happiness). Given that unpleasant life conditions are associated with psychological distress ( Hassanzadeh et al, 2017 ) and somatic symptoms ( Shahini et al, 2021 ), happiness is expected to be theoretically related to somatic symptoms and psychological distress. Hence, the more individuals are distressed and somaticised from negative life circumstances, the less they would feel happy.…”
Section: Introductionmentioning
confidence: 99%